Genetic Variants in KIR/HLA-C Genes Are Associated With the Susceptibility to HCV Infection in a High-Risk Chinese Population - Shen, Chao; Ge, Zhijun; Dong, Chen; Wang, Chunhui; Shao, Jianguo; Cai, Weihua; Huang, Peng; Fan, Haozhi; Li, Jun; Zhang, Yun; Yue, Ming (Frontiers in Immunology, 2021)
Background: KIR/HLA-C signaling pathway influences the innate immune response which is the first defense to hepatitis C virus (HCV) infection. The aim of this study was to determine the association between the genetic polymorphisms of KIR/HLA-C genes and the outcomes of HCV infection in a high-risk Chinese population. Methods: In this case-control study, four single nucleotide polymorphisms (SNPs) of KIR/HLA-C genes (KIR2DS4/KIR2DS1/KIR2DL1 rs35440472, HLA-C rs2308557, HLA-C rs1130838 and HLA-C rs2524094) were genotyped by TaqMan assay among drug users and hemodialysis (HD) patients including 1378 uninfected control cases, 307 subjects with spontaneous viral clearance and 217 patients with persistent HCV infection. Bioinformatics analysis was used to functionally annotate the SNPs. Results: After logistic regression analysis, the rs35440472-A and rs1130838-A alleles were found to be associated with a significantly elevated risk of HCV infection (OR=1.562, 95% CI: 1.229-1.987, P<0.001; OR=2.134, 95% CI: 1.180-3.858, P= 0.012, respectively), which remained significant after Bonferroni correction (0.05/4). The combined effect of their risk alleles and risk genotypes (rs35440472-AA and rs1130838-AA) were linked to the increased risk of HCV infection in a locus-dosage manner (all Ptrend<0.001). Based on the SNPinfo web server, rs35440472 was predicted to be a transcription factor binding site (TFBS) while rs1130838 was predicted to have a splicing (ESE or ESS) function. Conclusion: KIR2DS4/KIR2DS1/KIR2DL1 rs35440472-A and HLA-C rs1130838-A variants are associated with increased susceptibility to HCV infection in a high-risk Chinese population.